Agama dan Kewarganegaraan : Minoritas Muslim dalam Masyarakat Hindu Bali - Eddy Setiawan (Institut Kewarganegaraan Indonesia, 2024)
Diversity and religiosity are manifested in almost all regions of Indonesia. Practically, there is no region that is homogeneous in terms of ethnicity, language and religion. Likewise, Bali, with a Hindu majority population, also has other religious minorities, among them are Muslims. The existence of Muslims in Bali has been recorded since Bali was ruled by various kingdoms and sustained until the formation of the Unitary State of the Republic of Indonesia. The identification process as citizens is shared by both Balinese Hindus and residents of other groups such as Muslims who form the Muslim minority on the island. Civic relations in Bali appear to be going well, as reflected in the Religious Harmony Index released by the Ministry of Religion in 2023. In the index, Bali Province scored 77.95 that makes it one of the top 5 regions with the highest index scores after East Nusa Tenggara (81,027), Papua (80,20), North Sulawesi (78,35), and West Papua (78.63). This index based its score on three indicators, namely tolerance, equality and cooperation between religious communities. This article discusses the relationship between religion and citizenship in Bali by focusing on the main issues: firstly, the value system of Balinese Hindu society which was formed by the long interactions with various entities that has shaped a tolerant character until its advancement after the Bali Bombings I and II. Secondly, the formation process of Bali’s Muslim minority and thirdly, the dynamics of the relationship between the two groups during the democratization period which was marked by decentralization and the strengthening of identity politics, by examining the interactions between the two groups on the issue of Ajeg Bali. Hereby, it is expected that the conceptualization, development and practice of religion and citizenship in Bali can offer a new insight into navigating the relationship between the different communities in Indonesia.